Significance of clay art therapy for psychiatric patients admitted in a day hospital - Aquiléia Helena de Morais; Simone Roecker; Denise Albieri Jodas Salvagioni; Gabrielle Jacklin Eler (Investigación y Educación en Enfermería, 2014)
Objective. To understand the significance of clay art therapy for psychiatric patients admitted in a day hospital. Methodology. Qualitative, descriptive and exploratory research, undertaken with 16 patients in a day hospital in Londrina, in the state of Parana, Brazil, who participated in seven clay therapy sessions. Data collection took place from January to July 2012 through interviews guided by a semi structured questionnaire and the data were submitted to content analysis. Results. Three themes emerged: Becoming familiar with clay art therapy; Feeling clay therapy; and Realizing the effect of clay therapy. Conclusion. The use of clay as a therapeutic method by psychiatric patients promoted creativity, self-consciousness, and benefited those who sought anxiety relief.